Optimalisasi Pengelolaan Arsip Pegawai Negeri Sipil Melalui Digitalisasi Data: Implementasi Web Siasn Pada Kantor Regional X Badan Kepegawaian Negara Denpasar - Komang Ayu Kusumasanti; Ni Nyoman Menuh; Ida Bagus Ngurah Wimpascima; Nyoman Parta (Journal of Innovation Research and Knowledge, 2026)
The digitalization of personnel records is a crucial component of bureaucratic transformation toward the implementation of the Electronic-Based Government System (SPBE). This study aims to analyze the optimization of civil servant (PNS) records management through data digitalization at the Regional Office X of the National Civil Service Agency (BKN) in Denpasar. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the optimization of records management was carried out through three main stages: recording personnel records in Google Sheets, cross-verifying data using the SIASN Web application, and reorganizing both physical and digital records. The digitalization process significantly improved data accuracy, enhanced the efficiency of records retrieval, and supported the integration of personnel data into the national civil service information system. However, its implementation continues to face several challenges, including limited network infrastructure and discrepancies between physical records and digital data. Therefore, strengthening information technology infrastructure, accelerating the digitalization of personnel records, and developing more comprehensive standard operating procedures are essential to improve the quality and effectiveness of personnel records management